(untitled) (Materiali di Estetica. Terza serie, 2018)
This article is not intended to be an essay upon the thought of Alfredo Civita, it is rather a contribution upon two psychiatrists (Eugenio Borgna and Giovanni B. Cassano) who both helped me from different perspectives to approach the world of psychiatry and psychotherapy. They have also influenced the way I received the thought of Alfredo Civita and they played a role in the interior dialogue I entertained and still do entertain with him. They were also present once that I met him. I don’t have any specific psychiatric competence; I have read books upon the subject and I personally experienced psychotherapy talks. It is above all the way Civita talked to me and the way he conducted himself that caused me to write this contribution.